Pendekatan Etnografis dan Psikologis dalam Studi Islam - Achmad Fadil (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2020)
Abstract In order to get better understanding about Islamic Study is a knowladge for those who seek and wants to get better about Islamic as a religion in a deeper context which its consist of several aspects, because it’s not enough to getting understand about Islam as a religion with only relying to Alqur’an and alsa hadits, which it means theres also some sources that act as intermediary to tell us about Islam as a religion. One of the method is to take a look into the etnography and psychology of Islam. Etnography is a knowladge that telling us about the culture of muslim in Islamic way, while psychology enclousure is the knowladge that discuss about the psychology and mind of a human in Islam perspective. Keyword: Culture, Psychology/Mind, Islam